BUDAYA BIROKRASI PEMERINTAHAN ( Keperihatinan dan Harapan ) - Yusrialis Yusrialis (Lembaga penelitian dan pengabdian kepada Masyarakat, 2012)
Bureaucratic culture of government will parse about how the spread of cultural values and the level of commitment to the core members of the bureaucracy of the values that exist, and how cultural change in the government bureaucracy. Reality on the ground shows that the spread of cultural values has begun to appear even less so members Bureaucracy knowing the values embodied in the organization, because government officials already there are some who are happy to be starting the task and try to be the best, understand the purpose of the bureaucracy, the opportunity communication and relationships between superiors and subordinates and others although not epektif, as well as encouragement from the organization to the employee commenced. Level of commitment of the core members of the bureaucracy to the existing values (core values) are low because employees tend to bide her work and looked risky and troublesome work, the motivation to seek only employee status and salary, even indifferent to public facilities that they use even employees only serve an easy affair and promising material. Bureaucratic culture changes that occur precisely less objective, there is no congruence between employee goals with the Bureaucracy. Opportunity to give an opinion is sometimes there, even self-identification means that poor employee or employer organizations do not understand the behavior of individuals and expertise of employees in the organization.